Development of STEM-Based Physics E-Teaching Materials in the Context of South Sumatra Local Wisdom for High School Students - Ketang Wiyono; Ismet; Abidin Pasaribu; Evelina Astra Patriot; Sri Mindia Vanessa Pratiwi; Masayu Husnul Khotimah; Rahma Putria Anjani (Postgraduate, University of Mataram, 2025)
This study aims to validate physics teaching materials in the form of STEM-based e-modules in the context of local wisdom of South Sumatra. This type of development research uses the Rowntree development model which consists of 3 stages, namely the planning, preparation, and evaluation stages. This research uses tessmer formative evaluation. Then, the research instrument used was a validation sheet with data collection techniques using a Likert scale and a Guttman scale. The validation data was analyzed by determining the average of each assessment. The results showed that STEM-based physics teaching materials in the context of South Sumatra's local wisdom were in the valid and very valid categories, with results for product 1 e-modules for content aspects of 81%, media design 74% and language 76%. Product 2 e-LKPD for content aspects 73%, media design 77% and language 74%. Product 3 e-modules for material aspects 93.5%, design and language 93.25% as well as learning design 88.75%. Thus, it can be concluded that STEM-based physics teaching materials in the context of local wisdom of South Sumatra are valid, the three products have met the standards and criteria that have been set.